Using Edible Plant and Lightweight Expanded Clay Aggregate (LECA) to Strengthen the Thermal Performance of Extensive Green Roofs in Subtropical Urban Areas - Yi-Yu Huang; Tien-Jih Ma (Energies, 2019)
Gazing at natural landscapes and participating in agricultural activities can elicit psychophysiological restoration. However, most buildings are constructed merely to meet the minimum legal requirements for structure weight load. Extensive green roofs consisting of vegetables and a lightweight growth medium can be designed to provide not only passive-cooling effects on bare rooftops, but also to convert idle rooftops into temporary retreats for stressed individuals. The purpose of this study is to both measure the surface temperature reduction and heat amplitude reduction of a bare rooftop using the extensive green roofs containing a lightweight expanded clay aggregate (LECA) and Ipomoea batata as well as conduct a weight-reduction-and-cost analysis to measure the weight loss of the extensive green roofs incurred through LECA replacement. A four-stage field experiment was performed on the flat rooftop of a dormitory in a subtropical climate during summer. The results indicated that roofs with Ipomoea batata had a significantly higher passive-cooling effect than did roofs without Ipomoea batata. The roofs with 10%⁻40% LECA exhibited a slightly higher passive-cooling effect than did roofs with conventional garden soil. At a slightly different average air temperature (0.56 °C; i.e., 32.04 °C minus 31.48 °C), the combined effects of LECA and Ipomoea batata helped to significantly reduce the average temperature of the bare rooftop by an additional 10.19 °C, namely, temperature reduction of the bare rooftop increased from 9.54 °C under a roof with 0% LECA and without plants in the second stage to 19.73 °C under a roof with 10% LECA and with plants in the fourth stage.